2013
DOI: 10.5836/ijam/2013-04-05
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scale, intensity and farm structure on the income efficiency of Irish beef farms

Abstract: Data envelopment analysis (DEA) was employed to develop a model of income and scale efficiency for Irish beef farms. The objective was to identify and quantify management, farm structural and intensity indicators of efficiency for over 400 representative farms over two production systems and two years. Bootstrapping techniques were employed to measure and correct efficiency scores for sampling bias. Less than 10% of the sample exhibited constant or increasing returns to scale. The remaining farms exhibited dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The Irish beef supply chain is characterised by diverse actors spanning inputsuppliers, farmers, and numerous sales outlets, processing, distribution and retailing outlets. Figure 1 illustrates the complexity of the Irish beef supply chain and the heterogeneity of beef production systems at farm-level (Finneran and Crosson, 2013). There is wide-ranging heterogeneity in the Irish beef herd in terms of the systems (for example cattle rearing, cattle finishing), types of beef animals (ranging from suckler cows, calves, heifers, young cattle, bulls and steers) and breed variety (see Figure 1) (Hocquette and Chatellier, 2011;Finneran and Crosson, 2013).…”
Section: The Irish Beef Sectormentioning
confidence: 99%
“…The Irish beef supply chain is characterised by diverse actors spanning inputsuppliers, farmers, and numerous sales outlets, processing, distribution and retailing outlets. Figure 1 illustrates the complexity of the Irish beef supply chain and the heterogeneity of beef production systems at farm-level (Finneran and Crosson, 2013). There is wide-ranging heterogeneity in the Irish beef herd in terms of the systems (for example cattle rearing, cattle finishing), types of beef animals (ranging from suckler cows, calves, heifers, young cattle, bulls and steers) and breed variety (see Figure 1) (Hocquette and Chatellier, 2011;Finneran and Crosson, 2013).…”
Section: The Irish Beef Sectormentioning
confidence: 99%
“…However, this study showed that larger farms apply less efficient input-saving technology, so H:FS1 was rejected. In two recent studies, Manevska-Tasevska et al (2013) and Finneran and Crosson (2013) found respectively that Swedish and Irish beef production exhibit decreasing returns to scale, implying that farms are larger than the optimal scale. In both cases, structural changes rather than scale changes are suggested.…”
Section: Determinants Of Input-saving Technologymentioning
confidence: 99%
“…However, feeding lower levels of concentrate increases the income efficiency of e.g. Irish beef farms (Finneran and Crosson 2013). Overall, grazing is typically considered the most cost-effective way of meeting the nutritional needs of cattle.…”
Section: Farm Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The Irish beef supply chain is characterised by a diverse range of actors spanning input-suppliers, farmers, multiple animal sales outlets, processing, distribution and retailing outlets. The Irish beef supply chain is characterised by heterogeneity of beef production systems at farm-level (for example cattle rearing, cattle finishing), types of beef animals (ranging from suckler cows, calves, heifers, young cattle, bulls and steers) and breed varieties [17][18][19].…”
Section: The Irish Beef Sectormentioning
confidence: 99%